Ergonomic considerations when slotting piece-pick operations in distribution centers. - Lavender, Steven A.; Sun, Chunyi; Xu, Yilun; Sommerich, Carolyn M. (Applied Ergonomics, 2021)
Many warehouse slotting algorithms have overlooked worker ergonomics. This research aimed to develop ergonomics slotting guidelines based upon the back and shoulder postures and electromyographic (EMG) responses of the deltoid and erector spinae muscles when individual items are picked from, or full cases replenished to, different shelf heights In the first study of two studies, participants lifted small items representative of piece-pick tasks from seven shelf heights. In the second study, participants performed a simulated full case replenishment task in which they lifted boxes weighing between 2.7 and 10.9 kg from a cart into a flow rack. Shelf height significantly affected all postural and EMG variables and there was a trade-off between back and shoulder muscle activity across the varying shelf heights. Together, these studies were used to develop some general ergonomic slotting guidelines that could be implemented to reduce biomechanical load exposures experienced by distribution center workers.